2020
DOI: 10.5424/sjar/2019174-14682
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships between local Brazilian goat breeds based on mtDNA D-loop region similarity

Abstract: Aim of study: Our objective was to investigate the mitochondrial DNA of local Brazilian goats to gain insights into the genetic composition of this precious genetic resource.Area of study: The study was developed in BrazilMaterial and methods: We analyzed a hypervariable region of the mitochondrial DNA of 83 goats belonging to four local Brazilian breeds, including Canindé (CAN-RN), Moxotó (MOX-CE), Marota (MAR-PI) and Azul (AZU-PE) as well as of exotic breeds raised in different states of the Federation. Sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…Many studies reported lineage A as an old lineage, widely distributed in Asian, European and African goat breeds (Pereira et al, 2005;Royo et al, 2009;Vacca et al, 2010). Recently, investigations of domestic goats in Brazil (Silva et al, 2019) and Arabia (Al-Araimi et al, 2017) reported that most belonged to maternal lineage A. More than 90% of the world's goats were identified as belonging to lineage A (Wang et al, 2015;Deng et al, 2018;Ganbold et al, 2020;Nguluma et al, 2021).…”
Section: Analysis Of Phylogenymentioning
confidence: 99%
“…Many studies reported lineage A as an old lineage, widely distributed in Asian, European and African goat breeds (Pereira et al, 2005;Royo et al, 2009;Vacca et al, 2010). Recently, investigations of domestic goats in Brazil (Silva et al, 2019) and Arabia (Al-Araimi et al, 2017) reported that most belonged to maternal lineage A. More than 90% of the world's goats were identified as belonging to lineage A (Wang et al, 2015;Deng et al, 2018;Ganbold et al, 2020;Nguluma et al, 2021).…”
Section: Analysis Of Phylogenymentioning
confidence: 99%
“…As pesquisas retratam caprinos das raças locais: Moxotó, Azul, Canindé, Repartida, Marota e Graúna, os estudos ocorreram no Nordeste do Brasil (GINJA et al, 2017;MENEZES et al, 2020;MOURA et al, 2019;NERI et al, 2018;PAIM et al, 2019;SILVA et al,2019).…”
Section: Resultsunclassified
“…A grande variedade de cabras locais representa um importante reservatório genético e que áreas distantes dos centros de domesticação apresenta uma diversidade genética significativa que pode beneficiar os programas de conservação (SILVA et al, 2019). Os autores continuam descrevendo que esses resultados podem ser adequados para a criação de um programa de conservação estratégico, potencialmente beneficiando futuros programas de melhoramento.…”
Section: Resultsunclassified
“…The genetic makeup of the Brazilian goat breeds has been influenced by breeds of the Iberian Peninsula and even West African [ 21 , 30 , 31 , 32 ], promoting gene flow between the Iberian Peninsula, northern Africa, and the Canary Islands and Cape Verde [ 33 , 34 , 35 ]. Currently, Brazilian goat breeds are genetically distinct with a clear differentiation even from their possible ancestors [ 1 , 6 , 36 , 37 , 38 ]…”
Section: Resultsmentioning
confidence: 99%
“…The genetic makeup of the Brazilian goat breeds has been influenced by breeds of the Iberian Peninsula and even West African [21,[30][31][32], promoting gene flow between the Iberian Peninsula, northern Africa, and the Canary Islands and Cape Verde [33][34][35]. Currently, Brazilian goat breeds are genetically distinct with a clear differentiation even from their possible ancestors [1,6,[36][37][38] As pointed out before, the Brazilian goat herds are very concentrated in one specific region, so that gene flow among breeds must be shared, especially considering that the herd book is either not ongoing or is very rudimentary.…”
Section: Populationsmentioning
confidence: 99%